Perceptual Learning at Higher Trained Cutoff Spatial Frequencies Induces Larger Visual Improvements - Wu, Di; Zhang, Pan; Li, Chenxi; Liu, Na; Jia, Wuli; Chen, Ge; Ren, Weicong; Sun, Yuqi; Xiao, Wei (Frontiers in Psychology, 2020)
It is well known that repeated practice of a perceptual task can improve visual performance, termed perceptual learning. The goal of the present study was to evaluate the dependency of visual improvements on the features of training stimuli (i.e., spatial frequency). Twenty-three observers were divided into training and control groups.Visual acuity (VA) and contrast sensitivity function (CSF) were measured and compared before and after training. All observers in the training group were trained in a monocular grating detection task near their individual cutoff spatial frequencies. The results showed that perceptual learning induced significant visual improvement, which was dependent on the cutoff spatial frequency, with a greater improvement magnitude and transfer of perceptual learning observed for those with higher spatial frequencies. However, VA significantly improved following training but was not related tothe cutoff spatial frequency. The results may have major implications for the understanding of the nature of the learning rule and the neural plasticity of different cortical areas.